THE STUDY OF CRYSTALLOGRAPHIC PARAMETERS OF NANODISPERSE MODIFIERS - A. V. Kalinin; A. S. Dudnikov; A. V. Kashenkova (Литьë и металлургия)
The crystallographic parameters of dispersed and nanodispersed refractory compositions based on Ti, Al, Si, Mg were studied in the article. The nanocomposites were made by plasma chemical synthesis method. The specific surface area, grain size and phase analysis of nanocompositions were calculated. An analysis was made of the impurities effect on the properties of nanocompounds.